Design of Intelligent Parking System Based on Internet of Things and Cloud Platform - Yang, Jie; He, Jinbao; Wang, Xiongwei (International journal of grid and high performance computing, 2023)
The growing number of vehicles in a densely populated smart city results in a significant lack of parking space. During the implementation of systems for visibility of parking space vacancies for drivers, the bulk of the systems are focused on expensive dedicated sensor devices, requiring high installation costs. The emergence of a relatively inexpensive internet of things (IoT) system allows embedded cameras to track parking spaces' utilisation. However, parking space positions' manual specification before drivers can use such devices after implementation is important even for camera-captured images. Hence in this paper, IoT assisted intelligent parking system (IoT-AIPS) with cloud platform has been proposed to reduce vehicle parking waiting time and enhance accurate vehicle position prediction. The proposed method utilizes the machine learning method to classify topologies in the parking space based on stationary location.